As dimensões da escrita em texto de instrução ao sósia: produção textual de alunos do ensino fundamental: anos iniciais - Siqueira, Jucelaine Riquinha Gossler (2023)
This work aims to analyze a text, produced in a research situation, about the teacher's work in teaching written production in the Portuguese Language discipline in the early years of Basic Education. For Dolz, Gagnon, and Decândio (2010), learning written production serves as a condition for integration into the student's social and professional life. Thus, to understand the complexity that involves this knowledge, we start from the assumption that the teacher's object of work "is to create and organize an environment that is favorable to the development of certain abilities of the students and the learning of certain contents correlated to them" (MACHADO; BRONCKART, 2009, p. 39). We follow the methodological approach of Activity Clinic, proposed by Clot (2006, 2007, 2010) and Clot et al. (2006), which aims, through dialogue about work, to expand workers' power to act with methods that strengthen the work collective. From the point of view of the Activity Clinic, the collective is a fundamental instrument that enables the work to be sustained. Based on this methodology, we use instruction to the double to produce data for this research, which is one of the methods developed by Activity Clinic. Thus, this research seeks to analyze in the transcribed text produced from the method of instruction to the double, the highlighted topics and verbs or verbal expressions that configure a teacher's ways of acting used by her when giving instructions on teaching textual production to children. This method makes it possible for the teacher to provide instructions to another teacher who, hypothetically, would replace her in her work and may bring to light ways of acting in the face of difficulties at work. Based on the analyses, it is possible to identify that, to develop the teaching of writing, several fundamental components are necessary, which must be related to the dimensions of writing, which involve psychological, language and social phenomena. According to Dolz, Gagnon, and Decândio (2010), the attention given to the language components in a written production is a priority. However, in a global view of teaching, the psychological and social dimensions cannot be neglected. Thus, from the selected topics of the instruction to the double text that shows these dimensions, from the psychological point of view, it is possible to observe that the instructions given thematize the child, who mobilizes thoughts and affections when representing the knowledge and thematic contents about the activity requested by the teacher, seeking to integrate elements of their imagination and their cognitive abilities. Regarding the affective dimension linked to motivation, the teacher acts in the sense of talking and trying to calm the children, focusing on the proposed task. From the perspective of the language phenomenon, the teacher's instructions concentrate on elements of a narrative and the organization of structures necessary for the child to produce a text. In turn, from the point of view of the social phenomenon, the relationship with the cultural and interactional aspects is evident, which refers to the social place of the child for the representation of the drawing. Regarding the ways of teaching, it is observed that the teacher-instructor organizes ways to develop her class, identified by acting language, acting instrumental, and acting affective. Thus, analyzing language about work can lead to a better understanding of the teaching action in teaching written production, in this case, for the initial series.